1998
DOI: 10.1074/jbc.273.10.5591
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Cellular Retinaldehyde-binding Protein in the Retinal Pigment Epithelium

Abstract: Cellular retinaldehyde-binding protein (CRALBP) is abundantly expressed in the retinal pigment epithelium (RPE) and Mü ller cells of the retina, where it is thoughtto function in retinoid metabolism and visual pigment regeneration. Mutations in human CRALBP that destroy retinoid binding have been linked to autosomal recessive retinitis pigmentosa. To identify the DNA elements that regulate expression of the human CRALBP gene in the RPE, transient transfection studies were carried out with three CRALBP-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Our results are also in agreement with those of Yu et al (21), who showed that in transgenic mice carrying four tandem copies of the PCE-1/Ret1 element fused to the lacZ reporter gene, ␤-gal was expressed not only in photoreceptor cells, but also in the ganglion cell layer and ciliary epithelium. The PCE-1 element in the 5Ј-flanking region of cellular retinaldehyde-binding protein may play a important role in the expression of cellular retinaldehyde-binding protein in RPE cells (22). In addition, present supershift analysis suggested that the PCE-1 site bound to RX as well as some other factor(s).…”
Section: The Pce-1 Element Interacts With the Product Of An Eyementioning
confidence: 56%
“…Our results are also in agreement with those of Yu et al (21), who showed that in transgenic mice carrying four tandem copies of the PCE-1/Ret1 element fused to the lacZ reporter gene, ␤-gal was expressed not only in photoreceptor cells, but also in the ganglion cell layer and ciliary epithelium. The PCE-1 element in the 5Ј-flanking region of cellular retinaldehyde-binding protein may play a important role in the expression of cellular retinaldehyde-binding protein in RPE cells (22). In addition, present supershift analysis suggested that the PCE-1 site bound to RX as well as some other factor(s).…”
Section: The Pce-1 Element Interacts With the Product Of An Eyementioning
confidence: 56%
“…The retinal pigment epithelium (RPE) 4 is essential for supporting the survival and function of retinal photoreceptor cells (1). One of the key functions of the RPE is enzymatic regeneration of the photoreceptor visual chromophore (11-cis-retinal) through the visual cycle, a cyclical pathway consisting of a series of enzymatic reactions in which each step converts retinoid intermediates into a substrate for the next step (2).…”
mentioning
confidence: 99%
“…Major RPE-expressed components of the visual cycle are three enzymes (RPE65, LRAT, and RDH5), two retinoid carrier proteins (RLBP1 and RBP1), and a modulator (RGR), which work sequentially to regenerate and continuously supply 11-cis-retinal to retinal photoreceptors. Although efficient functioning of the visual cycle requires coordinated expression of its various components and some progress has been made in defining the cis-regulatory elements involved in transcriptional regulation of individual visual cycle genes such as Rpe65 and Rlbp1 (3)(4)(5)(6)(7), only limited studies have addressed the regulatory mechanisms that coordinate expression across the visual cycle genes.…”
mentioning
confidence: 99%
“…The human RPE65 5Ј-upstream region has also been studied using sequence analyses, cell transfection assays, and DNase I footprinting (24). Analysis of the 5Ј-up-stream region of the human cellular 11-cis-retinaldehyde-binding protein gene (RLBP1), which is preferentially expressed in RPE and Muller cells, suggested that a photoreceptor consensus element-1 (PCE-1, CAATTAG) located in the proximal promoter region might act as a positive regulator of RPE gene expression (25). This is interesting because PCE-1 was generally considered a photoreceptor element, and a sequence similar to PCE-1 is also present within the proximal promoter region of both human and murine Rpe65; however, its biological relevance has not yet been experimentally tested.…”
mentioning
confidence: 99%